Literature Review: Pengaruh Edukasi Terhadap Pengetahuan dan Kepatuhan Mengonsumsi Obat pada Pasien Diabetes Mellitus - Dini Mardhiyani; Juwana janu (STIKes Ibnu Sina Ajibarang, 2025)
Diabetes Mellitus (DM) is a chronic disease that requires long-term adherence to treatment. One of the main challenges in managing type 2 DM is the low level of patient adherence to medication. This literature review aims to analyze the effect of health education on improving patients’ knowledge and medication adherence. The review is based on selected scientific articles that discuss the relationship between education, knowledge, and adherence in patients with DM. Findings indicate that health education-delivered through counseling, printed media, self-instructional modules, or home visits—generally improves patients’ understanding of the disease and the importance of regular treatment. This increase in knowledge contributes to better health behavior, particularly in terms of medication compliance. Interactive educational methods that involve healthcare providers and patient families are more effective than one-way communication approaches. Structured and continuous education tailored to patient characteristics has the potential to significantly enhance disease management. Therefore, health education should be prioritized as a key strategy to improve treatment adherence and prevent long-term complications in patients with diabetes mellitus.